2003
DOI: 10.1051/0004-6361:20021789
|View full text |Cite
|
Sign up to set email alerts
|

Doppler imaging of stellar surface structure

Abstract: Abstract. We present the first Doppler image for both stellar components of the F9+G0 ZAMS binary σ 2 CrB and found evidence for the coexistence of cool and warm spots on both stars. Cool spots appear mainly at polar or high latitudes while a confined equatorial warm belt appears on the trailing hemisphere of each of the two stars with respect to the orbital motion. We also present an update of the TempMap imaging code that allows us to solve the stellar surface temperature distribution on both binary componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 36 publications
(38 reference statements)
9
56
1
2
Order By: Relevance
“…We conclude that there is significant spot coverage on the inner hemisphere (white dwarf facing side of the M star) observed on all maps. This spot distribution -where there is a higher density of spots on the hemisphere facing the companion star -is similar to that observed in many other systems, such as the pre-CV V471 Tau (Hussain et al 2006), the eclipsing binary ER Vul (Xiang et al 2015), and the close binary σ 2 CrB (Strassmeier & Rice 2003). Furthermore, Kriskovics et al (2013) suggested that the hot-spots mapped on the companion-facing hemisphere in V824 Ara may indicate the strong interaction between the magnetic fields of the component stars, as is commonly observed in close RS CVn-type binaries.…”
Section: Surface Mapssupporting
confidence: 84%
“…We conclude that there is significant spot coverage on the inner hemisphere (white dwarf facing side of the M star) observed on all maps. This spot distribution -where there is a higher density of spots on the hemisphere facing the companion star -is similar to that observed in many other systems, such as the pre-CV V471 Tau (Hussain et al 2006), the eclipsing binary ER Vul (Xiang et al 2015), and the close binary σ 2 CrB (Strassmeier & Rice 2003). Furthermore, Kriskovics et al (2013) suggested that the hot-spots mapped on the companion-facing hemisphere in V824 Ara may indicate the strong interaction between the magnetic fields of the component stars, as is commonly observed in close RS CVn-type binaries.…”
Section: Surface Mapssupporting
confidence: 84%
“…At the same time the cool polar spot had a large appendage near the phase of conjunction with the secondary behind in 1996/97, but less determinable in 1997/98. A comparable spot dependency on orbital location was seen on the active close binary σ 2 CrB (Strassmeier & Rice 2004). σ 2 CrB is a F9+G0 ZAMS binary.…”
Section: Discussionmentioning
confidence: 52%
“…An integration time of 600 s per exposure gave a peak S /N of 300:1 per resolution element. For a brief description of the data reduction, we refer to the paper by Strassmeier & Rice (2003). The data log summary is given in Table 1.…”
Section: Cfht/gecko Spectroscopy In 2000mentioning
confidence: 99%